Remote sensing technology in mapping socio-economic divergence of Europe - Mikhailov, Andrey; Mikhaylova, Anna; Alsynbaev, Kamil; Bryksin, Vitaliy; Hvaley, Dmitry (Bulletin of Geography. Socio-economic Series, 2021)
Marine and ocean coasts traditionally act as natural growth poles for the humankind. Recent studies conducted by scholars from both natural and social sciences suggest that coastal zones accumulate population, agglomerate industries, attract entrepreneurs, and pull investments. The coastalization effect remains to be one of the defining factors of regional development around the globe and is projected to strengthen within a quarter of a century. Deepening socio-economic inequality and polarization between countries and regions despite of efforts taken with the convergence policies puts the ‘marine factor’ on research agenda. The study holds a comparative evaluation of the coastalization processes across the regions of Europe using the remote sensing technology and the statistical multivariate analysis for testing the correlation level of the results obtained. The research is based on a dataset for 413 regions of Europe featuring indicators for population density and Gross Regional Product (GRP) in Purchasing Power Parity (PPP) per sq.km. The regions are grouped into clusters depending on their socio-economic indicators and the intensity of nocturnal illumination. Results suggest that coastal and inland region types evenly distribute between clusters, with an average of 40% coastal. Observations over nocturnal illumination clearly indicate an extensive anthropogenic impact on European coasts, both northern and southern. However, their overall luminosity is inferior to inland territories. The study concludes with four patterns derived from a combined methodology of socio-economic indicators and remote sensing.